2019
DOI: 10.3904/kjim.2018.056
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes in acute myocardial infarction patients with versus without any cardiovascular risk factors

Abstract: Background/Aims Although cardiovascular (CV) risk factors are well established, some patients experience acute myocardial infarction (AMI) even without any risk factors. Methods We analyzed total 11,390 patients (63.6 ± 12.6 years old, 8,401 males) with AMI enrolled in Korea Acute Myocardial Infarction Registry-National Institute of Health from November, 2011 to December, 2015. Patients were divided into two groups according to the presence of any CV risk factors (group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…MI is one of the primary causes of human death and the pathophysiological mechanism of myocardial injury after MI has been a hot research topic in the field of cardiovascular disease [ 1 ]. Several pathophysiological mechanisms explain the occurrence and development of myocardial injury after myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MI is one of the primary causes of human death and the pathophysiological mechanism of myocardial injury after MI has been a hot research topic in the field of cardiovascular disease [ 1 ]. Several pathophysiological mechanisms explain the occurrence and development of myocardial injury after myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial infarction (MI) is caused by acute coronary occlusion and leads to myocardial injury in the corresponding blood supply area [ 1 ]. Acute MI still frequently leads to heart failure and contributes to cardiovascular morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…However, data documenting the clinical outcomes of patients without any SMuRFs are still limited and the underlying mechanisms for the increased mortality rate among this group of patients are not clear. Moreover, current evidence is predominantly from highly developed countries, where patients can homogeneously receive high-quality emergency medical service and standardized evidence-based clinical management [ 7 14 ], whereas, in China, a large proportion of patients might experience long pre-hospital delays and suboptimal medical care, especially in those low-level hospitals and remote areas [ 15 ]. A recent study even reported that the rate of reperfusion eligibility decreased among patients with STEMI from 2011 to 2015 in China, which was majorly driven by the increased prevalence of long pre-hospital delay [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial ischaemia has become one of the most common causes of death and disability in modern society (Berliner et al 2018). Clinical ischaemic heart disease is frequently accompanied by angina pectoris and myocardial infarction (Choi et al 2019). A recent study demonstrated that myocardial ischaemia contributed to myocardial necrosis as well as cardiomyocyte apoptosis (Ran et al 2015).…”
Section: Introductionmentioning
confidence: 99%